Divergent Paths: Civil Service Employment Relations in Australia and Canada - Gurdon, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This article describes the legislated strengthening of employee involvement in decision-making within the federal civil service in Australia. While the quite distinct differences between the two industrial relations Systems must be recognized, particularly the resulting distribution of power between the government as employer and its employees, aspects of the general philosophy underlying the Australian model may find some useful applications as the Canadian public sector Systems continues to evolve.